New directions in social policy evidence from the Indonesian Health Insurance Programme - Mulyadi Sumarto; Alexandra Kaasch (United Nations Research Institute for Social Development (UNRISD), 2018)
This paper discusses the development of Indonesia's health insurance programme as a lens through which to understand Indonesian social policy development. The Indonesian health insurance programme has experienced considerable development despite fluctuating economic growth and political upheaval. Indonesia initiated its health insurance programme during the Soekarno period (1945-1966) by providing health insurance to formal workers. However, this period of economic austerity saw the programme poorly implemented. As the economy improved under Soeharto (1966-1998), the health insurance programme steadily improved until 1997, when the Asian financial crisis hit Indonesia. The crisis forced the Indonesian government to take a loan from the World Bank, which required the establishment a social safety net for the poor. The safety net programme led to massive development of social protection programmes, which encouraged the government to implement a universal health coverage programme. This paper describes the characteristics of Indonesia's social policy development, analyses its relationship with economic policy, highlights its key drivers and identifies the interests and alliances that shaped Indonesia's social policy.
Keywords: 330; social policy; health insurance; economic growth; the World Bank; Asian economic crisis; Indonesia